(3GdfaM GdeYfhj aj GdehdO GdfHhjs - (3GdCRgQj, eMeO Hf eMeO GdeZQHjs
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd TgQ QHjY GdChd ZQI TghQ GdYGe hGdUdGI hGdSdGe Ydi SjOfG eMeO GdPj HehdOg Ye GdSYhO Ydi LejY GdCfGes
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO cdeG PcQg GdPGcQhf hZad Yf PcQg GdZGadhf SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs